Intra-Articular Corticosteroid Injections to Manage Trapeziometacarpal Osteoarthritis—a Systematic Review. (December 2015) - Fowler, A.; Swindells, M. G.; Burke, F. D.
Background: Osteoarthritis of the trapeziometacarpal joint (TMJ) is a common condition causing significant disability. The aim of this study is to ascertain whether an intra-articular corticosteroid injection leads to pain relief and increased function and what is the duration and magnitude of this effect. Methods A systematic review with a critical appraisal of identified studies that met the inclusion criteria was performed. Two authors performed the literature review by independently searching the Cochrane, PubMed and Google Scholar databases. Results: A total of 118 relevant articles were found, but only nine studies met the inclusion criteria which included 4 double-blinded randomised control trials (RCTs) and 5 prospective case series. There is some evidence in the literature to support the efficacy of steroid injections into the TMJ. Most studies do suggest a good short-term benefit. However, one identifies no benefit over placebo but two studies found a benefit lasting at least 6 months. Conclusions: This study demonstrates that there are potentially significant although short-term benefits to be gained from steroid injections into the TMJ. They can lead to pain relief and improved function, certainly in the first 1 to 3 months post-injection. Steroid injections are a low-risk procedure and are helpful in delaying or avoiding the need for surgery.